The problems of existentialism in the works of Muhammad Khaidar Dulati - Zhamyliya Amirkulova, Zhambul Myrzabekov, Gulzhikhan Nurysheva,; Dombaycı, Mehmet Ali; Spanov, Meirhan (Opción, 2019)
This article will show the system of cultural and historical value belonging to the deeply rooted Turkic civilization and its special place in world civilization via comparative qualitative research methods. As a result, Dulati was considered to be an expert with encyclopedic knowledge, especially of oral literature, and it was clearly demonstrated through the poem „Jahanname‟. We came to the conclusion that Dulati‟s ideas about life merge with religion.